Twitter: Party Leader Debate May 2014 - Språkbanken Text (University of Gothenburg, 2024)
Material from Twitter, collected during the party leader debate on May 4th 2013 and a few days before and after

Material från Twitter, insamlat under partiledardebatten 4 maj 2014 samt några dagar före och efter
Twitter: Partiledardebatt maj 2014
Keywords: Language Technology (Computational Linguistics); corpus; Natural Language Processing; Språkbehandling och datorlingvistik